HPLC analysis and extraction method of SN-38 in brain tumor model after injected by polymeric drug delivery system - Pinunta Nittayacharn (2018)
© 2014 by the Society for Experimental Biology and Medicine. SN-38 is a highly potent anticancer drug but its poor solubility in aqueous solvent and adverse side effects limit clinical applications. To overcome these limitations, SN-38-loaded-injectable drug delivery depots have been intratumorally administered in xenograft tumor model in nude mice. The extraction and high performance liquid chromatography (HPLC) were performed in order to determine the amount of SN-38 inside tumors. SN-38 was extracted from tumors using DMSO. HPLC analysis was validated and resulted in linearity over the concentration range from 0.03 to 150 µg/mL (r2≥ 0.998). Lower limit of detection (LLOD) and lower limit of quantitation (LLOQ) were 0.308 µg/mL and 1.02 µg/mL, respectively. The extraction efficiency (% recovery) of SN-38 in porcine tissues was similar to that of tumors which provided more than 90% recovery in all concentrations. Moreover, the variability of precision and accuracy within and between-day were less than 15%. Therefore, this extraction and HPLC protocol was applied to determine the amount of SN-38 in tumors. Results show higher remaining amount of SN-38 in tumor from SN-38-loaded polymeric depots than that of SN-38 solution. These results reveal that SN-38-loaded polymeric depots can prevent the leakage of free-drug out of tumors and can sustain higher level of SN-38 inside tumor. Thus, the therapeutic efficacy can be elevated by SN-38-loaded polymeric depots.